1975
DOI: 10.1083/jcb.65.1.237
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of the high molecular weight proteins associated with in vitro-assembled brain microtubules

Abstract: Microtubules isolated from brain extracts by in vitro assembly (1, 19, 23) are composed principally of two tubulins and two high molecular weight proteins (microtubule-associated proteins [MAPS] 1 and 2) (2,5,7,20). Recently, it was demonstrated that in vitro-assembled brain microtubules (neurotubules) are coated with filaments (5, 7) which are similar to the filaments attached to neurotubules in situ (4, 15, 21, 24, 25), and it was suggested that the filaments are composed of the higher molecular weight MAPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(91 citation statements)
references
References 24 publications
5
86
0
Order By: Relevance
“…7), immunoelectrophoresis (30), and immunodiffusion (data not shown) . The results summarized above confirm the proposal that the cytoplasmic microtubules have associated with their surfaces one or more characteristic proteins called MAPs, a term coined previously by Sloboda et al (32) to refer to a class of high molecular weight proteins that are stoichiometrically associated with the tubulin subunit lattice of in vitro assembled vertebrate brain microtubules (10,19,24,30,33). The term MAP has since come to refer to a general class of proteins that associate with and appear to modulate some of the characteristics of in vitro assembled brain microtubules .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…7), immunoelectrophoresis (30), and immunodiffusion (data not shown) . The results summarized above confirm the proposal that the cytoplasmic microtubules have associated with their surfaces one or more characteristic proteins called MAPs, a term coined previously by Sloboda et al (32) to refer to a class of high molecular weight proteins that are stoichiometrically associated with the tubulin subunit lattice of in vitro assembled vertebrate brain microtubules (10,19,24,30,33). The term MAP has since come to refer to a general class of proteins that associate with and appear to modulate some of the characteristics of in vitro assembled brain microtubules .…”
Section: Discussionsupporting
confidence: 74%
“…wall of the microtubule in a manner analogous to that previously described for brain microtubules (2,10,19,24) .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition to tubulin these preparations also contain microtubule-associated proteins (MAPs) that bind to microtubules with high affmity, and correspond to hairlike projections on microtubule surfaces (8,22). These observations and the fact that neuronal cells exhibit microtubule-dependent motility in the form ofaxonal transport have led to much speculation that MAPs may function as microtubule crossbridges in the cell.…”
mentioning
confidence: 99%
“…Microtubule-associated proteins (MAPS) are known to form filamentous structures projecting from the surfaces of microtubules (DENTLER et al, 1975;MURPHY and BORISY, 1975). SUPRENANT and DENTLER (1982) demonstrated that MAPS can form connections between a pancreatic secretory granule and isolated brain microtubules.…”
Section: Preparationsmentioning
confidence: 99%